2016
DOI: 10.1039/c6nj02175a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of two-dimensional carbon dots decorated with molybdenum oxide nanoflakes with various phases

Abstract: Demonstrated novel synthesis of two dimensional MoO3 nanoflakes decorated by C-dots. Unique optoelectronic properties revealed at longer wavelength (850 nm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The obtained dark blue powder was used for further characterization. This blue color has been seen previously for nanosized MoO 3 …”
Section: Methodsmentioning
confidence: 99%
“…The obtained dark blue powder was used for further characterization. This blue color has been seen previously for nanosized MoO 3 …”
Section: Methodsmentioning
confidence: 99%
“…Carbon quantum dots were prepared by an eco-friendly microwave-assisted method, which is analogous to the CD synthesis in previous reports [47, 48]. In a typical production, 17.1 g of sucrose was dissolved in deionized water to prepare 1 M sucrose solution.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30] Research work have indicated that molybdenum oxide (MoO 3 ) has various forms: one of them is the thermodynamic and stable phase of orthorhombic α-MoO 3 , [11][12][13] and the others are metastable phases of monoclinic β-MoO 3 , [31] hexagonal h-MoO 3 . [32,33] The conversion of the stoichiometric MoO 3 into nonstoichiometric oxygen deficiency molybdenum oxide (MoO 3-x ) since that the becoming of heterovalent heteroatoms or lattice vacancies or lattice vacancies [34,35] have excellent advantages, such as electrical conductivity, catalytic properties, optical properties and so on, to be achieved by controlling and adjusting the valence state of molybdenum element [36,37] which will be applied in various science fields. Furthermore, increased with oxygen hole, the color of MoO 3-x arrange from blank to obvious blue with an valid LSPR absorption in NIR.…”
Section: Introdutionmentioning
confidence: 99%